STING-dependent sensing of self-DNA drives silica-induced lung inflammation. Issue 1 (December 2018) - Benmerzoug, Sulayman; Rose, Stéphanie; Bounab, Badreddine; Gosset, David; Duneau, Laure; Chenuet, Pauline; Mollet, Lucile; Bert, Marc; Lambers, Christopher; Geleff, Silvana; Roth, Michael; Fauconnier, Louis; et al.
Abstract Silica particles induce lung inflammation and fibrosis. Here we show that stimulator of interferon genes (STING) is essential for silica-induced lung inflammation. In mice, silica induces lung cell death and self-dsDNA release in the bronchoalveolar space that activates STING pathway. Degradation of extracellular self-dsDNA by DNase I inhibits silica-induced STING activation and the downstream type I IFN response. Patients with silicosis have increased circulating dsDNA and CXCL10 in sputum, and patients with fibrotic interstitial lung disease display STING activation and CXCL10 in the lung. In vitro, while mitochondrial dsDNA is sensed by cGAS-STING in dendritic cells, in macrophages extracellular dsDNA activates STING independent of cGAS after silica exposure. These results reveal an essential function of STING-mediated self-dsDNA sensing after silica exposure, and identify DNase I as a potential therapy for silica-induced lung inflammation. Silica particles induce intereukin-1 (IL-1) response to contribute to lung inflammation, but the underlying mechanism is unclear. Here the authors show that silica induces cell death and release of mitochondria and genomic DNA, which are sensed by STING with or without involving cGAS, respectively, for IL-1 induction and lung inflammation.